PENERAPAN PASAL 112 AYAT (1) JO PASAL 114 AYAT (1) UU NO 35 TAHUN 2009 TENTANG NARKOTIKA BAGI PENGEDAR SABU DI WILAYAH HUKUM POLRES PROBOLINGGO - RIZAL AHMAD JABBAR (Dinamika, 2021)
ABSTRACT Narcotics Abuse is a crime that misuses narcotic substances. One of them is methamphetamine which is a class I narcotic substance. In other words, the circulation of the substance is strictly prohibited.The problem faced now is how to apply article 112 paragraph (1) in conjunction with article 114 paragraph (1) of Law No. 35 of 2009 on Narcotics, what are the obstacles and strategies of the police in uncovering a case of narcotics abuse, especially methamphetamine dealers in the legal area of the Probolinggo Police.The research method used in this research is the empirical juridical method. Based on the results of the research, for its application in the jurisdiction of the Probolinggo Police, the police are appropriate based on the statements of the suspects when interrogated, witnesses, evidence and by the incident in the incident location. Second, obstacles in the case of disclosing drug dealers. Obstacles in the field are the lack of cooperation in the community regarding the illicit trafficking of drugs to the police. There are many ways and efforts made by the Probolinggo Police, one of which is by conducting an intensive investigation of the perpetrators, victims and witnesses.Keywords : Narcotics Misuse, crystal meth, Probolinggo Regional Police ABSTRAK Penyalahgunaan Narkotika merupakan kejahatan yang menyalahgunakan zat – zat narkotika. Salah satunya sabu yang termasuk zat narkotika golongan I. Dengan kata lain zat tersebut sangat dilarang pengedarannya.Masalah yang dihadapi sekarang adalah bagaimana penerapan pasal 112 ayat (1) jo pasal 114 ayat (1)  UU No 35 tahun 2009 tentang Narkotika, apa saja hambatan dan strategi kepolisian dalam mengungkap sebuah kasus penyalahgunaan narkotika khususnya pengedar sabu diwilayah hukum Polres Probolinggo.Metode penelitian yang digunakan dalam penelitian ini adalah metode yuridis empiris Berdasarkan hasil penelitian, untuk penerapannya diwilayah hukum Polres Probolinggo pihak kepolisian sudah sesuai berdasarkan keterangan tersangka ketika diinterogasi, saksi, barang bukti dan oleh kejadian perkara dilokasi kejadian. Kedua, hambatan dalam kasus pengungkapan pengedar narkoba. hambatan dilapangan yakni kurang kooperatifnya masyarakat terkait peredaran gelap narkoba kepada pihak kepolisian. Banyak cara dan upaya yang dilakukan pihak Polres Probolinggo, salah satunya dengan melakukan penyelidikan secara intensif baik terhadap pelaku, korban maupun para saksi.Kata Kunci : Penyalahgunaan Narkotika, Sabu, Polres Probolinggo